Proposta de um sistema integrado de gestão em segurança de tráfego - SIG SET - Mantovani, Vívian Ramirez (Universidade Federal de São Carlos, 2003)
This work presents a management tool that can be of great utility to private or governmental organizations, mainly the ones which are really considered to deal with the transit in a new, modern, efficient, efective and, over all, responsible way. For this, it makes use of modern computational techniques, as is the case of Geographic Information System - GIS, beyond the technique of benchmarking, an important basis of the Management of Total Quality. The Integrate Management System of Traffic Safety called SIG SET, developed for strategical level, produces ideas and concepts that take into account the management of transit security in a wide-ranging, sistemic and based on the information form. The SIG SET offers four databases and can operationally be implemented in integrated or modular form. For organizations with still a small structure, the implantation can start from the Database of Traffic accidents BDA, that uses a manager of relational database. However, with the evolution of this practice, the necessity of the implantation of a Space Database of Road System-BDSV arises , that own, amongst others, attributes of the interventions of the ways and volumes of traffic. In a subsequent stage, the georeferenced database of accidents can be implanted in software GIS (BDS). This new mentality of management, ripened and consolidated , the space database of benchmarking can be implemented (BDB). The BDB will be able to contain socioeconomic, social, cultural, human attributes, fleets of vehicles and accident rates of cities, states, regions or countries. The information of the databases must lead to the development of procedures that set up comparisons with pertinent referentials (benchmarking) and that have more positive security levels. This would stimulate the continuous improvement of road security, with the establishment of realistic and challenging goals of small, medium and long run. Based on the information generated by SIG SET, one can purpose interventions in the three traditional areas that compose the transit security: Education, Enforcement and Engineering; as well as to execute the verification of the effectiveness and efficiency of the same ones. The technique of benchmarking can periodically be carried out, applying the (re)evaluation of goals. The SIG SET unfolded for the operational level will produce, as a result, thematic reports and maps with the information of the databases produced. SIG SET is a tool indicated in the aid of taking decisions of governmental managing agencies and of organizations linked to the management of road security. An application of method SIG SET is presented in operational level, with the aim of exemplify its potentiality.
Keywords: Segurança viária; Benchmarking (administração); Sistema de informação geográfica; Banco de dados; Traffic safety; Benchmarking; GIS; Databases; ENGENHARIAS::ENGENHARIA DE TRANSPORTES